Analisis Kinerja Keuangan dan Ekonomi Pemerintah Daerah Sebelum dan Setelah Pemekaran - Salim, Muhamad Nur (Universitas Negeri Semarang, 2019)
The expansion in 2008 generate 30 new autonomous region of 21 parent area. Papua is a region with the second largest carrier regions undergoing expansion in 2008 that is as much as four regional carriers. Four areas of the stem has abundant natural resources, which if managed with optimal will make an impact on donations of original income areas to areas in Papua region. But in point of fact many areas in Papua which is undergoing expansion in 2008 has a low degree of fiscal decentralization before and after undergoing expansion. This indicated a still low level of contributions to the total income of the PAD area. The purpose of this research was to analyze financial performance differences in the degree of fiscal decentralization aspect and the financial independence of the region as well as the performance of the economy in the aspect of the growth of GDP per capita and the degree of poverty before and after undergoing expansion. The sample in this study consists of four district/parent area in Papua. This research method using statistical analysis descriptive quantitative analysis techniques with test paired sample t-test. The result there is a significant difference to the level of poverty in all districts, there is a significance to the growth of GDP per capita in the Regency of Puncak Jaya, and there was no significant difference in financial performance, namely the degree of fiscal decentralization and financial independence of the area before and after the expansion. Pemekaran pada tahun 2008 menghasilkan 30 daerah otonomi baru dari 21 daerah induk. Papua adalah wilayah dengan daerah induk terbanyak kedua yang mengalami pemekaran pada tahun 2008 yaitu sebanyak empat daerah induk. Ke-empat daerah induk tersebut mempunyai sumber daya alam yang melimpah, yang apabila dikelola dengan optimal akan memberi dampak pada sumbangan pendapatan asli daerah bagi daerah di wilayah Papua. Namun pada nyatanya banyak daerah di Papua yang mengalami pemekaran tahun 2008 memiliki nilai derajat desentralisasi fiskal yang rendah sebelum dan setelah mengalami pemekaran. Hal ini mengindikasikan masih rendahnya kontribusi PAD terhadap total pendapatan daerah. Tujuan penelitian ini untuk menganalisis perbedaan kinerja keuangan dalam aspek derajat desentralisasi fiskal dan kemandirian keuangan daerah serta kinerja ekonomi dalam aspek pertumbuhan PDRB per kapita dan tingkat kemiskinan sebelum dan setelah mengalami pemekaran. Sampel dalam penelitian ini terdiri dari empat kabupaten/ daerah induk di Papua. Metode penelitian ini menggunakan analisis statistik deskriptif kuantitatif dengan teknik analisis uji paired sample t-test. Hasilnya terdapat perbedaan yang signifikan untuk tingkat kemiskinan di semua kabupaten, terdapat signifikansi pada pertumbuhan PDRB per kapita di Kabupaten Puncak Jaya, dan tidak terdapat perbedaan yang signifikan pada kinerja keuangan yaitu derajat desentralisasi fiskal dan kemandirian keuangan daerah sebelum dan setelah mengalami pemekaran.